(untitled) (Research, Society and Development, 2024)
West Syndrome (WS) is an epileptic encephalopathy that manifests itself in children, depending on age. It is characteristic of infantile spasms that can occur in flexion, extension, or mixed pattern. In addition to these contractions, affected individuals generally experience delayed neuropsychomotor development. Taken together, the electroencephalogram (EEG) of the patients reveals a specific interictal pattern known as hypsarrhythmia, which is an important marker for diagnosing the syndrome. Since its discovery, there has been intense debate about the most effective treatment options for WS. Adrenocorticotropic hormones, corticosteroids, valproic acid and antiepileptic drugs, such as vigabatrin, are some of the most frequently used therapeutic approaches. This present study aims to contribute to research on the best treatment strategies for West Syndrome, based on a careful analysis of 18 articles selected from the scientific platforms Scientific SciELO, PubMed and LILACS.